(untitled) (Journal of Fiber Bioengineering and Informatics, 2026)
This study evaluates the dyeing performance of cotton fabric with a natural dye extracted from the heartwood of Senna siamea, focusing on the effects of anodic electrochemical pretreatment combined with varying concentrations of two mordants: potassium aluminium sulfate (alum) and calcium hydroxide. Sodium chloride (10 g/L) was maintained as the auxiliary in all dye baths, while mordant concentrations ranged from 0 to 20 g/L for both alum and calcium hydroxide. Colourimetric analysis (CIE Lab*) revealed that alum treatment generally lightened the fabric and decreased colour saturation, with ∆E values reaching 13.11 at 20 g/L, indicating a shift toward washed-out shades. In contrast, calcium hydroxide enhanced fabric brightness and significantly increased yellow chroma, producing warmer and more vibrant hues, particularly at 10 g/L, which was visually the lightest and showed the greatest colour difference (∆E = 14.32). Washing fastness (ISO 105-C10) remained consistently good (ratings 3-4/5) across all mordant types and concentrations. Rubbing fastness (ISO 105-X12) improved with increasing mordant concentration, especially for alum at 15-20 g/L and calcium hydroxide at 10 g/L, with wet rubbing ratings improving from 2/3 to 3/4. These results highlight the distinct influences of alum and calcium hydroxide on colour development and durability, offering practical insights for optimising natural dyeing with Senna siamea extract. The study promotes accessible, eco-friendly dyeing techniques suitable for rural artisans, enhancing traditional textile quality and supporting sustainable production.